Palang Pintu Kereta Api Pneumatik Otomatis Berbasis PLC Omron CP1E-NA20DR-A - Ari Widodo; Wahyu Sapto Aji (Buletin Ilmiah Sarjana Teknik Elektro, 2019)
One alternative in reducing accidents at railroad crossings without guards is automatic pneumatic railroad crossings. This tool uses PLC (Programmable Logic Controller) as a processing system. Automatic crossing railroad crossing works by using two proximity sensors that are placed on the right and left crossings with a distance far from the crossing (approximately 1 KM). The system outputs are pneumatically actuated sirens, lights and door lintels. At most this door will move up and down closing and opening the crossing. The use of pneumatics in manufacturing because pneumatics saves more space around the crossing and is safe. In testing, detection is done in 2 opposite directions. The results show the tool has been working to close and open crossings with good performance.Salah satu alternatif dalam mengurangi kecelakaan di pintu perlintasan kereta api tanpa penjaga adalah palang pintu kereta api pneumatik otomatis. Alat ini menggunakan PLC (Programmable Logic Controller) sebagai sistem pemroses. Palang pintu perlintasan kereta api otomatis bekerja dengan menggunakan dua buah sensor proximity yang di letakkan pada kanan dan kiri perlintasan dengan jarak yang jauh dari perlintasan (kurang lebih 1 KM). Keluaran sistem berupa aktifnya sirene, lampu, dan palang pintu yang digerakkan dengan pneumatik. Paling pintu ini akan bergerak naik dan turun menutup dan membuka perlintasan. Penggunaan pneumatik dalam pembuatan karena pneumatik lebih menghemat ruang sekitar perlintasan dan aman. Dalam pengujiannya, pendeteksian dilakukan dengan 2 arah yang berlawanan. Hasil menunjukkan alat telah bekerja menutup dan membuka perlintasan dengan kinerja yang baik.